The Understanding Programming Languages in Programming Algorithms - Dewi, Rahmawati; Purba, Nery Adelia; Kartika, Tia Dwi; Meitiara, Sri; Hutabarat, Sotar Ferdinan (Jurnal Warta Dharmawangsa, 2026)
A programming algorithm is a coherent progression that is followed to address a specific problem or task. A programming language is a guide used to convey tasks to a computer. Programming languages include: C, C++, Java, Python, JavaScript. Each programming language has its own advantages and disadvantages. This article is expected to provide a broad understanding of the programming languages used in programming algorithms. The method used is a literature study which presents a programming language that is easiest to learn for beginners.